The Existence of Hyang Waringin Temple in Kubu Customary Village: (Perspective of Hindu Religious Education) - Cana Artha, I Made; Pitriani, Ni Rai Vivien (Jayapangus Press, 2024)
A harmonious relationship with God can be realized by thanking, devotion (Bhakti), and belief (Sraddha). Human devotion to God is realized by building a sacred building or temple. There are several temples with unique and high religious values in Bali, especially Hyang Waringin Temple. This temple is located in Kubu Pakraman Village, Bangli District, Bangli Regency. The existence of this temple is unique, which has unique traditions, such as the Ngusabha ceremony during Sasih Kaenem, Nimbang Sanganan Kukus Injin tradition, and the implementation Yadnya tradition held at Hyang Waringin temple led by Jro Mangku because of the Siva Bhuda concept. This study used several methods: observation, interviews, documentation, and literature. All collected data were reduced, displayed, and verified. The results showed that (1) Hyang Waringin Temple was a public temple, and the existence of this temple was closely related to the Kehen Temple’s history in Bangli. (2) The procession of religious ceremony tradition in Hyang Waringin Temple was the community’s gratitude and joy for the abundance of His grace of traditions. (3) The meaning of the religious ceremony tradition at Hyang Waringin Temple from the perspective of Hindu religious education, namely the meaning of Tattwa, Ethical, ritual, Tri Hita Karana, Socio-religious, and Tattwamasi education. This study found that Hyang Waringin Temple in Kubu Pakraman Village still exists and has religious traditions nowadays. It became a reflection for the Kubu Pakraman Village community to increase the high religiosity aspect, which is expected to increase the community’s belief (Sradha) and devotion (Bhakti).